Overview of the TREC-2002 Web Track - Craswell, Nick; Hawking, David (Proceedings of TREC-2002, 2002)
The TREC-2002 Web Track moved away from non-Web relevance ranking and towards Webspeciﬁc tasks on a 1.25 million page crawl “.GOV”. The topic distillation task involved ﬁnding pages which were relevant, but also had characteristics which would make them desirable inclusions in a distilled list of key pages. The named page task is a variant of last year’s homepage ﬁnding task. The task is to ﬁnd a particular page, but in this year’s task the page need not be a home page.
://research.microsoft.com/users/nickcr/pubs/craswell_trec02wt.pdf